Risk of recurrent venous thromboembolism in patients with autoimmune diseases: data from the Registro Informatizado de Enfermedad TromboEmbólica (RIETE) registry. (2nd June 2021) - Borjas Howard, Jaime; Ruiz‐Sada, Pablo; de Leeuw, Karina; López‐Jiménez, Luciano; Font, Carme; Marchena, Pablo Javier; Madridano, Olga; Debourdeau, Philippe; Meijer, Karina; Monreal, Manuel
Summary: Autoimmune disease is a risk factor for first incident venous thromboembolism (VTE). However, data on the risk of recurrent VTE in people with autoimmune disease is sparse. We explored the risk of recurrent VTE using the RIETE registry, comparing people with autoimmune disease ( n = 1305) to those without ( n = 50608). Overall rates were 6.5 and 5.1 recurrent VTE/100 years for patients with autoimmune disease vs controls, respectively. After adjustment for sex and unprovoked/provoked VTE yielded an adjusted hazard ratio of 1.29 (95%CI 1.03‐1.62). The analysis was limited by short median follow up time (161 days overall), precluding definitive conclusions on recurrent VTE risks.